2021
DOI: 10.1016/j.heliyon.2021.e06739
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects and modeling of some processing parameters on milling, cooking, and sensory properties for Nigerian rice using a one-step rice milling machine

Abstract: s This study investigates the interactive effects of processing parameters on the quality of milled rice using a one-step milling machine. Also, predictive models were generated using response surface methodology. The processing parameters were moisture content (10–14 % dry basis), shaft speed of rotation (600–900 rpm), and polishing time (1–3 min). The quality parameters evaluated were milling (head rice yield, percentage broken rice, fine broken rice, and milled rice yield), cooking (optimum cooki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…As aforementioned, the paddy is composed of three layers: the husk on the outside, rice bran in the annular portion, and white rice in the centre [119]. Although there are a wide variety of rice processing methods available, each of which produces a different rice quality, it has been observed that the fundamentals of rice production remain the same [120,121]. Rice processing entails a series of steps that must be completed correctly, using various methods and equipment [122].…”
Section: Rice Processingmentioning
confidence: 99%
“…As aforementioned, the paddy is composed of three layers: the husk on the outside, rice bran in the annular portion, and white rice in the centre [119]. Although there are a wide variety of rice processing methods available, each of which produces a different rice quality, it has been observed that the fundamentals of rice production remain the same [120,121]. Rice processing entails a series of steps that must be completed correctly, using various methods and equipment [122].…”
Section: Rice Processingmentioning
confidence: 99%